Cultural Clusters as a Local Economic Development Strategy in Rural, Small Town Areas: The Sarah Baartman District in South Africa. - Drummond, Fiona; Snowball, Jen (Bulletin of Geography. Socio-economic Series, 2019)
Theory suggests that the cultural and creative industries (CCIs) cluster in cities where levels of socio-economic development are higher and where they can take advantage of the city’s hard and soft infrastructure. However, some South African rural areas and small towns have identified the CCIs as potential economic drivers. This paper investigates the relationship between the presence of CCIs in non-metropolitan spaces and levels of socio-economic development using a municipal level socio-economic status index and GIS mapping. Results show that there is a positive relationship between larger numbers of CCIs and higher levels of development. It is suggested that a threshold level of development must be met before the CCIs will cluster in an area and become a viable option for promoting local economic development.